(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2022)
In this paper, inspired by the idea of Suzuki type α^+ F-proximal contraction in metric spaces, we prove a new existence of best proximity point for Suzuki type α^+ F-proximal contraction and α^+ (θ-φ )-proximal contraction defined on a closed subset of a complete metric space. Our theorems extend, generalize, and improve many existing results.